Keanekaragaman Serangga Nokturnal Berdasarkan Warna Lampu Perangkap Cahaya di Balai Penelitian Tanaman Sayuran Desa Tongkoh Sumatera Utara - Muhammad Tirta Rizky; Melfa Aisyah Hutasuhut; Zahratul Idami; Fatiani Manik (Jurnal Biologi dan Pembelajarannya (JB&P), 2023)
Nocturnal insects are a type of insect that is active at night and plays a role in maintaining the balance of the ecosystem and has an ecologically and economically occurring role. This study was conducted to determine the diversity, evenness, and dominance of nocturnal insects based on the color of the light trap lamp at the Vegetable Crop Research Center of Tongkoh Village, Karo Regency, North Sumatra. This study used the light trap method by making a transect 100 m long and on the transect, 5 observation stations were installed. There are 27 insect families consisting of 35 types of nocturnal insects with a total of 240 individuals. The most common type of insect found is Empoasca fabae. The diversity index (H') is included in the moderate category with a value of 2.10 on the green lamp trap, 1.38 on the blue lamp trap, 2.23 on the yellow lamp trap, 2.76 on the white lamp trap, and 2.26 on the red lamp trap, this shows that the insect diversity at the study site is in a stable condition. The dominance index (C) is categorized as low with a value of 0.184 on green light traps, 0.347 on blue lamp traps, 0.222 on yellow light traps, 0.092 on white light traps, and 0.150 on red light traps. This situation occurs because there is no type of nocturnal insect that is too dominant so that the diversity of insects is classified as being in a stable state.